Analysis Approach on Travel Time due to Changes on Airport Network Function - Iif Ahmad Syarif; Ervina Ahyudanari (Jurnal Transportasi: Sistem, Material, dan Infrastruktur, 2018)
The plan to expand the service of the airport in the province of North Borneo will be executed in 2020 and 2030. The expansion planning would affect the routes and network existing of air transportation in the province of North Borneo. The change on route networks will affect to function and travel time between the existing routes. This study aims to determine the suitability of the existing condition of the airport in the form of the distance between theairport and the change of travel time due to changes in the function of the airports. The distance between the airport will be determined through the coordinate data of each airport and calculated using distance analysis based on Euclidean distance. The results are then drawn into the distance matrix. Travel time of each route includes the process of taking off, climbing,cruising, descending, approaching, and landing. Changing routes also affect the passenger travel time between cities. The result indicates that travel time and travel cost before and after changing on airport function bring some divergence.